TO STUDY THE PERCEIVED BARRIERS AND MOTIVATORS FOR DELAYED ACCEPTANCE OF FIRST DOSE OF COVID-19 VACCINATION: A SINGLE CENTRE STUDY - GUPTA MEGHNA; NAVJOT, KAUR; K, GUPTA VITULL; PRANAV, SINGLA; MEENAKSHI, SINGLA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: COVID-19 pandemic has triggered an unprecedented global scientific collaboration to develop COVID-19 vaccines which is the most effective way to defeat COVID-19 pandemic. The WHO has identified vaccine hesitancy as a grave global health threat and even after 7 months of free vaccination program, India is lagging behind to achieve the targets essential for herd immunity. Hence, we initiated this survey to study the perceived barriers and motivators for delayed acceptance of first dose of COVID-19 vaccination. Methods: A survey was conducted during free COVID-19 vaccination camps using a pretested, validated, and anonymous pro forma including eight questions regarding perceived barriers and six regarding perceived motivators for acceptance of the first dose of COVID-19 vaccination and valid responses were analyzed according to age groups and gender. Results: During our survey, 1144 valid responses were received and analyzed. Results showed fear of side effects as the most sighted barrier among study population, gender, and age groups. Compulsory requirement of vaccination for joining job/college was the most sighted motivator among study population, gender, and 18–30 years age group whereas fear of 3rd wave was most sighted motivator among 31–44 years, 45–59 years, and >60 years age group. Conclusion: In spite of free COVID-19 vaccine and intensive campaigns, it seems that adequate vaccination targets might not be achieved and results of our survey suggest needs for increased focus on the perceived barriers as well as the perceived motivators to increase vaccination acceptance.